The use of systematic reviews to justify orthopaedic trauma randomized controlled trials: A cross-sectional analysis. Issue 2 (February 2020) - Johnson, Austin L.; Walters, Corbin; Gray, Harrison; Torgerson, Trevor; Checketts, Jake X.; Boose, Marshall; Norris, Brent; Vassar, Matt
Highlights: New randomized controlled trials should be initiated if previous literature reviews indicate that a new trial is warranted. A well-designed randomized controlled trial should translate a clinical problem into a research question. Not consulting existing research prior to beginning a trial may lead to research waste. Abstract: Objective: Orthopaedic trauma is one of the largest surgical fields in medicine, and as such, requires the latest evidence to ensure the best standard of care. Systematic reviews are an invaluable resource that compiles an exhaustive summary of the most current evidence on a given clinical question. The primary aim of this study is to evaluate the use of systematic reviews as justification in conducting randomized controlled trials published in high impact orthopaedic trauma journals. Methods: We analyzed randomized controlled trials published in the top three high impact orthopaedic trauma journals between 2015 and 2018. We performed data extraction blind, independent, and in duplicative manner to ensure the validity of the findings. For each trial, data was extracted by the number of systematic reviews cited in each clinical trial and whether or not the study used a systematic review as justification for conducting the trial. A subgroup of general orthopaedic clinical trials were included for comparison. Results: Of 144 articles retrieved, 128 were included. Overall, 71.1% (91/128; [95% CI, 63.2–78.9]) of included orthopaedic trauma randomized controlled trials referenced a systematic review and 28.9% (37/128) of studies did not cite a systematic review. Of the 91 trials that referenced a systematic review, 33.0% (30/91; [95% CI, 23.3–42.6]) of RCTs cited a systematic review as trial justification, whether that be "verbatim" or "inferred". "Verbatim" justifications occurred in 20.0% (6/30; [95% CI, 5.7–34.3]) of included trauma RCTs that cited a systematic review as justification for conducting the trial and "inferred" justifications occurred in 80.0% (24/30; [95% CI, 65.7–94.3]). Conclusion: Systematic reviews are frequently cited in orthopaedic trauma RCTs but are not commonly cited as justification for conducting a clinical trial. Ideally, evidentiary uncertainty regarding a research question should be established by existing literature through a systematic review to reduce research waste.